Order of Magnitude of Multiple Fourier Coefficients (Analysis in Theory and Applications, 2013)
The order of magnitude of multiple Fourier coefficients of complex valued functions of generalized bounded variations like $(\Lambda^1,\cdots, \Lambda^N)BV^{(p)}$ and $r-BV$, over $[0, 2\pi]^{N},$ are estimated.